Students’ Experiences in an LMS‑Based Basic Reading Course: A Narrative Inquiry - Irwan Sulistyanto; Erwin Hari Kurniawan; Angga Prasongko; Wildan Isna Asyhar; Krisna Adi Prayoga (UIN Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2026)
This study explores first‑semester students’ experiences in navigating an LMS‑based Basic Reading course at an Indonesian university. The transition into digitally mediated reading instruction often introduces emotional, technical, and cognitive challenges for novice LMS users. Using a narrative inquiry approach, three students were interviewed to capture their learning trajectories, difficulties, and evolving perceptions across a 16‑session semester. The findings indicate that students initially struggled with LMS navigation, digital submission procedures, and unstable internet connectivity, which triggered confusion, anxiety, and fear of missing deadlines. As they gained procedural familiarity through repeated exposure, peer support, and independent exploration their confidence increased and emotional tension gradually decreased. The LMS was perceived to offer benefits such as centralized materials, flexible access, and efficient task management, although issues related to unclear notifications and inconsistent deadline settings remained problematic. This study highlights that LMS‑mediated reading instruction can enhance autonomy and accessibility for novice learners, but its effectiveness depends on reliable infrastructure, transparent digital guidelines, and structured onboarding to support students’ emotional and academic adjustment.